EXAMINATION IN AUDITING. - Beckert, Ralph F.; Meigs, Walter B. (The Accounting Review, 1965)
Abstract This article presents a question paper prepared by the auditing section of the American Institute of Certified Public Accountants (C.P.A) for November 1964 Uniform C.P.A. examination which held on November 5, 1964.